On Large Deviations of Multiplicative Functions - Kubilius, J.; Laurinčikas, A. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Й. Кубилюс, А. Лауринчикас. О больших уклонениях мультипликатных функций J. Kubilius, A. Laurinčikas. Multiplikatyvinių funkcijų didelių atsilenkimų klausimu